Contribuindo para a transição de uma instituição psiquiátrica - Centro de Reabilitação de Casa Branca-SP em um hospital Geronto/geriátrico - Caminotto, Arisson José de Lima (2008)
Elderly aged 60 and over are gradually gaining greater representation within the Brazilian population as a whole, is the growing increase in its proportion, as the economic and social implications that this fact implies. With an ageing population, is the remarkable increase in the number of elderly people seeking care because of problems of physical and mental health, and essential knowledge of the fact that population for the implementation of appropriate measures that result in aging and quality. According to epidemiological evidence on Geriatrics, as specialty, acquires key role in the public health system, both in relation to direct medical care to patients and the training of human resources in other areas involved in the process. This study proposes a project for the deployment of community service, open, regional reference of multidisciplinary and specialized care to the elderly. Because of ageing also occur in psychiatric institutions where there are long-stay patients and the lack of studies in the literature search, it was aimed to seek a new focus of analysis for deinstitutionalisation unit of study, the CRCB, then become a Centre Reference through a project of assistance to full health of the elderly in DRS - XIV